Treatment of the mother lenguage for the development of the environmental formation in Higher Education - Lisi Alicia Porro de Zayas; Lourdes de la Caridad Cabrera Reyes; Idalmis Batancourt Pérez; Manuel Moisés Pérez Hidalgo (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2019)
The present work has as objective to base diverse alternatives that, from the methodological point of view, have been put into practice for the environmental formation in Higher Education. The experience is a result of the research project Strategy for the animation and reading promotion in the university of pedagogic sciences with community approach assigned to the National Project Reading Universities: An initiative for the improving of the reading and literary formation of teachers, developed between September, 2013 until December, 2018 in the University of Ignacio Agramonte Loynaz, of Camagüey, Cuba.